The Role of Supply Chain Management in Improving Customer Service. (Field study in the International Company for Rolling Iron in Homs) - قاسم, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to determine the relationship between supply chain management and improving customer service in the International Iron Rolling Company in Homs, by demonstrating the role of senior management support, the participation of beneficiaries from the application of the supply chain management system, the clarity of the supply chain management system strategy, and the good selection of the supply chain management system. The study relied on the deductive approach as a general approach to research, and followed the descriptive analytical approach, where the questionnaire was distributed to 63 employees of the International Iron Rolling Company under study, and then a field study was conducted in order to demonstrate this relationship. The study concluded that there is a significant positive relationship between supply chain management and customer service. Then I presented a summary of the most important results that were reached, where the main and most important result was that the supply chain management relationships in the bank under study have a profound impact on customer service in all aspects, and the quality of this service can only be achieved through effective and successful management of the elements of the chain in the manner that achieve customer satisfaction.